Drivers of Cost of Treatment for Traumatic Spinal Cord Injury in Ibadan, Nigeria (2020)
Background: Traumatic Spinal Cord Injury (TSCI) is a costly condition in human and economic terms. Yet, studies on direct cost of treatment for TSCI in resource-constraint countries are sparse. Objective: To estimate the direct cost of treatment for patients with TSCI at the University College Hospital (UCH), Ibadan, Nigeria using an incidence-based costing approach. Methods: All new cases of TSCI admitted in the hospital from January, 2009 to December, 2013 were identified and reviewed. Direct costs of in-patient and out-patient treatments over the first year of injury were estimated. Results: 114 individuals with TSCI (73 males; 41 females) were admitted and discharged home alive from the hospital. The largest cost driver to the patients and the National Health Insurance Scheme was cost of consultations by neurosurgeons which constituted about a third (34.4%) of the total costs of treatment. Less than a fourth (24.2%) of the total cost of in-patient treatment was spent on therapeutic interventions (surgery, drugs and physiotherapy). There was a significant relationship between the direct cost of treatment and each of the severity of traumatic spinal cord injury and length of hospital stay (p = 0.01). Level of injury was not significantly associated with direct cost of treatment (p=0.89). Conclusion: Direct cost of treatment for individuals with TSCI in Ibadan, Nigeria is substantial. This high cost underscores the need for novel service models with potential for minimizing cost for patients with TSCI in Nigeria.